Contrast flow patterns based on needle tip position during cervical transforaminal epidural injections. Issue 3 (19th May 2021) - Levin, Josh; Levi, David; Gall, Nolan; Horn, Scott; Smuck, Matthew
Abstract: Background: Few studies have evaluated the effect of final needle position on contrast flow patterns during the performance of cervical transforaminal epidural steroid injections (TFESIs). Objective: To analyze fluoroscopically guided cervical TFESI contrast flow patterns based upon final needle tip position. Design: Retrospective, observational in vivo study. Setting: Outpatient private practice physical medicine and rehabilitation spine clinic. Participants: One hundred consecutive patients undergoing cervical TFESIs. Interventions: Cervical TFESIs. Main Outcome Measures: Categories of contrast flow patterns including epidural, intraforaminal, "sufficient to inject, " and "predominantly epidural and/or intraforaminal, " based upon final needle tip position. Results: Two independent observers reviewed images from 100 consecutive patients and classified injectate flow patterns stratified by needle tip position. The interrater reliability for all categories of interest was moderate, with kappa values from 0.61 to 0.76. More medially placed needles (middle third and lateral third of the articular pillars) resulted in higher rates of epidural contrast flow (75%; 95% confidence interval [CI]: 56%‐94%; and 60%; 95% CI: 47%‐73%) compared to needles placed lateral to the articular pillars (26%; 95% CI: 8%‐44%), and higher rates of "predominantly epidural and/or intraforaminal" flow patterns with needles placed in the middle one third (75%; 95% CI: 56%‐94%) and lateral one third of the articular pillars (47%; 95% CI: 34%‐60%) compared to flow patterns when needles were placed lateral to the articular pillars (17%; 95% CI: 2%‐32%). No needles were placed in the medial third of the articular pillars. Conclusions: More medially placed needle tips result in more optimal flow patterns during cervical TFESIs. The importance of this finding is unknown as clinical outcomes were not measured.